Microincision 25G Pars Plana Vitrectomy with Peeling of the Inner Limiting Membrane and Air Tamponade in Idiopathic Macular Hole. Issue 1 (January 2017) - Hejsek, Libor; Stepanov, Alexandr; Dusova, Jaroslava; Marak, Jan; Nekolova, Jana; Jiraskova, Nada; Codenotti, Marco
Purpose: To evaluate the success of a mini-invasive technique for operation of idiopathic macular hole (IMH). Methods: We retrospectively examined 29 patients (30 eyes) in whom 25-G pars plana vitrectomy (PPV), peeling of the inner limiting membrane (ILM), and application of air tamponade were performed. The group of the patients included 7 males and 22 females (76%), age range 57-79 years (median 70). The follow-up period was 3-47 months (median 17). Results: Pars plana vitrectomy was indicated only in the stages of full-thickness macular hole. Prior to operation, 13 eyes (43%) were in stage 2, 15 eyes (50%) in stage 3, and 2 eyes (7%) in stage 4. The IMH healed in 28 eyes after operation. Persistence of IMH occurred in 2 eyes (7%). After subsequent reoperation with extension of the peeling zone of the ILM and gas tamponade (with 10% C3 F8 ), these macular holes also healed (100%). Prior to carrying out PPV, best-corrected visual acuity (BCVA) ranged between 20/40 and 20/500 (median 20/125). At the end of the follow-up period, BCVA was improved to 20/40 (median). The change in the final BCVA compared to the initial visual acuity was statistically significant (p = 0.008; Wilcoxon). Conclusions: The 25-G PPV with peeling of the ILM and air tamponade is an effective technique and presents no increased risks in comparison with routine procedures. The main benefit of the intervention is its good tolerance by the patient, particularly with respect to painfulness and postoperative irritation.